Examining the Effects of Fortified Whey Protein Enteral Nutrition on Immune Response and Infection Risk - Ullah, Shakeeb; Faiqah Ramzan; Mubarik Ali; Norina Jabeen; Qamar Ullah (Indus Journal of Bioscience Research, 2025)
This study investigated the impact of a fortified whey protein enteral nutrition intervention on cytokine responses, nutritional biomarkers and infection rates in patients who were following breast cancer surgery. The randomized controlled experiment had 180 patients, who were allocated into two groups: intervention group received enteral nutrition enriched with whey protein, intended to augment immune function and boost nutritional status, while the control group received normal postoperative care. The intervention yielded substantial impacts on immunological and nutritional markers. Levels of cytokines, including IL-2, IL-4, IL-17 and IFN-gamma, as well as nutritional markers such as serum albumin and total protein, were evaluated at three time points: baseline, day 15 and day 30 after the surgery. The intervention group demonstrated significant elevations in cytokine levels, suggesting a strong improvement in the immune response. The nutritional indicators also showed notable enhancements, indicating improved overall nutritional well-being, which is essential for successful recuperation. Furthermore, the intervention resulted in a substantial decrease in both the frequency and intensity of surgical site infections, demonstrating its efficacy in enhancing therapeutic results. The findings indicated that the use of enriched whey protein enteral nutrition can have a substantial positive impact on the recovery of patients undergoing surgery. This is achieved by improving immune responses and raising nutritional status.